Proteolysis in human breast cancer. Issue 2 (1st April 2000) - Garbett, E A; Reed, M W R; Stephenson, T J; Brown, N J
Abstract : Background —The process of proteolysis is important at several stages of the metastatic cascade. A balance between the expression of the genes encoding endogenous proteinases and inhibitors exists and when the production of proteinases exceeds that of inhibitors proteolysis occurs. Aims —To determine whether differences in the profile and activity of proteinases and inhibitors exist within breast tumour tissue (n = 51), surrounding background breast tissue (n = 43), normal breast tissue from breast reduction mammoplasty operations (n = 10), and cells of the breast cancer cell line, MCF-7. Methods —Proteinase (matrix metalloproteinase 1 (MMP-1), MMP-2, MMP-3, MMP-9, urokinase-type plasminogen activator (uPA), and tissue-type PA (tPA)) and inhibitor (tissue inhibitor of metalloproteinases; TIMP-1 and TIMP-2) expression and proteinase activity were compared using substrate zymography, western blotting, immunohistochemistry, and quenched fluorescent substrate hydrolysis. Results —The presence of all proteinases and inhibitors was greater in breast tumour tissue when compared with all other types of breast tissue (p < 0.05). The activity of total MMPs as determined by quenched fluorescent substrate hydrolysis was also greater in breast tumours (p < 0.05). Conclusion —There is increased proteolysis in human breast tumours when compared with other breast tissues.